Transformasi Literasi Digital di Papua Barat Daya: Tantangan dan Strategi Pasca Pembentukan Daerah Otonomi Baru - Halik, Wahyudin; Rais, Lukman; Parera, Fhilipus Nery Marianus Lagan; Wato, Felix Salmon (Universitas Muhammadiyah Sorong, 2025)
The establishment of Southwest Papua Province through Law No. 29 of 2022 has created opportunities for digital literacy transformation, yet it continues to face complex structural, social, cultural, and geographical challenges. Disparities in internet access, limited digital devices, high data costs, low digital skills, and differing perceptions of technological benefits are primary obstacles to equitable digital literacy. This study aims to identify these barriers and formulate effective digital literacy strategies grounded in local wisdom. The research employs a mixed-methods approach with a Convergent Parallel design, combining a quantitative survey of 270 respondents and qualitative literature analysis to achieve a comprehensive understanding. Findings indicate that digital literacy among the population of Southwest Papua is hindered by economic factors, infrastructure limitations, technical capacity gaps, and cultural sensitivities. Effective strategies for enhancing digital literacy emphasize community participation, adaptation to local cultural values, gender inclusivity, youth empowerment, and the strengthening of technical, ethical, and digital cultural competencies. In conclusion, digital literacy transformation in Southwest Papua must adopt a holistic, contextual, and sustainable approach to empower communities, reinforce social cohesion, and support economic development and digital governance in the post-establishment era of the new autonomous region.